Alcohol in Native Communities and Deadly Identity Markers - Bernard Roy (Drogues, santé et société, 2005)
Alcohol consumption among native people has been an issue of concern since their very first contacts with Europeans. During the 20th century, medical dialogues took the place of the previous moral and legal approaches. Today, physicians and health professionals are on the front lines, working to control alcoholism and other drug addictions in native communities. This article describes two aspects. First, the author critiques the explanatory medical model of alcoholism among native people which persists in considering alcohol dependency as essentially a biological disease, one that requires constantly increasing amounts of medical and pharmaceutical resources. This critique offers the author a platform which then enables him to invest in an argument designed to show that alcoholism in native communities is firmly entrenched in their historical and political situation. Alcoholism reveals the significant social disparities and exclusion which have become part of the biological, social and political life of native people. The author suggests that alcoholic behaviour observed in native communities reveals a complex identification framework which, in certain cases, could be qualified as “deadly”. In this article, the act of drinking is presented as an unavoidable component of the act of eating, a completely social act feeding many points of view but most of all the “social and political body” of the native person in his daily life. La consommation d’alcool chez les Autochtones constitue un sujet de préoccupation depuis les tous premiers contacts avec les Européens. Au XXe siècle, le discours médical a pris la relève des approches morales et légales qui dominèrent les siècles précédents. Aujourd’hui, médecins et professionnels de la santé occupent une place de premier plan dans les mesures de contrôle de l’alcoolisme et autres toxicomanies en milieu autochtone. Les propos du présent article sont de deux ordres. Dans un premier temps, l’auteur s’investit dans une série de critiques qu’il porte sur le modèle explicatif ...